Agricultural trade liberalization under Doha: the risks facing African countries - Badiane, Ousmane (International Food Policy Research Institute, 2006)
African countries tend to be affected by global agricultural policies in the same way as other economies but with much more severe economy-wide repercussions... The present discussion paper 1) examines the vulnerability of Africa economies with respect to global agricultural trading policies and their induced changes in world agricultural markets, based on the above characteristics; 2) analyzes the efficiency effects within Africa’s agricultural sector of world market distortions resulting from agricultural trading policies; 3) illustrates the impact of global protectionism on poverty levels and distribution among rural households in Africa and the implication for the objective of poverty reduction; 4) reviews the options and risks facing African countries in their pursuit of opportunities for greater participation in the global trading system, in particular in connection with the Doha trade agenda; and 5) discusses options for global trade liberalization that would best benefit African economies. The paper argues that the insistence on the part of African countries on Special and Differential Treatment entails much more risks than benefits for their economies. It also indicates that trade preferences have been less beneficial to African economies than usually assumed and at any rate have not been significant enough to compensate African countries for the negative impact of global protectionism. Finally, the paper also disagrees with the widely accepted conclusion that African countries would suffer from liberalization of global agricultural policies because they tend to be net food importers. That conclusion does not sufficiently take into consideration the dynamic long term effects of global policy changes on production and trading patterns among African countries and the potential efficiency effects that would emanate there from.